2018
DOI: 10.1210/js.2018-00187
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Visceral Fat and Plasma Aldosterone Concentration in Patients With Primary Aldosteronism

Abstract: ContextThe involvement of visceral fat in aldosterone secretion has not been reported in patients with primary aldosteronism (PA). Patients with PA are complicated by metabolic syndrome more frequently than those without PA. An excess of visceral fat has been hypothesized to cause an elevation of aldosterone secretion in patients with PA.ObjectivesTo clarify the role of visceral fat in the pathophysiology of PA, we investigated the correlation between plasma aldosterone concentration (PAC) and visceral fat par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…This speculation might explain why our result showed longer term of excess aldosterone in patients with APA presented with smaller VFA. Among the population of non-PA, one study found the positive correlation between serum aldosterone levels and visceral obesity in healthy women 14 ; however, other studies from a large communitybased sample of non-PA patients 36 and a recent study of APA patients, 37 in agreement with our result, reveal that visceral adipose tissue was not associated with plasma aldosterone levels.…”
Section: Discussionsupporting
confidence: 90%
“…This speculation might explain why our result showed longer term of excess aldosterone in patients with APA presented with smaller VFA. Among the population of non-PA, one study found the positive correlation between serum aldosterone levels and visceral obesity in healthy women 14 ; however, other studies from a large communitybased sample of non-PA patients 36 and a recent study of APA patients, 37 in agreement with our result, reveal that visceral adipose tissue was not associated with plasma aldosterone levels.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, obesity has been suggested to induce hyperaldosteronism through the actions of adipocytokines; for example, activation of the sympathetic nervous system 10 . Shibayama et al 34 reported that there was a positive association between PAC and visceral fat area in patients with IHA. In the present study, as shown in the lower Matsuda index, insulin sensitivity was lower in IHA compared with APA with no difference in the presence of either obesity or central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate regression analysis showed that VF% and VFA are significantly associated with L/S ratio in patients with IHA, whereas PAC is not. We have previously reported that PAC is positively correlated with VF% and VFA in patients with IHA, but not in APA [25]. This may be because the univariate analysis, which showed a negative correlation between L/S ratio and PAC in patients with IHA, is influenced by visceral fat volume as a confounding variable.…”
Section: Discussionmentioning
confidence: 85%